Discovery and synthesis of N2,N4-substitued-cycloalkyl[d]pyrimidine 2,4-diamine analogs： The first examples of small-molecular FGFR-1 activator - Li, Bao-Li; Xiao, Fang; Lu, Wen-Chao; Sun, Yu-Yun; Zhu, Jin; Li, Jian (Chinese chemical letters, 2014)
A series of novel, cycloalkyl-modified pazopanib analogs 2 and 3 were designed and synthesized. Their kinase modulatory effects on FGFR-1, VEGFR-2, PDGFR-β and c-KIT were evaluated by the caliper mobility shift assay. Introduction of cycloalkyl into the pyrimidine linker of pazopanib almost abolished the four kinases inhibitory potency of compounds 2 and 3, but surprisingly, resulted in good activation effects on FGFR-1. Compounds 3d and 3g showed double-digit, nanomolar, selective activation effects on FGFR-1, and could be classified as first-generation small molecular activators of FGFR-1 kinase.